Śrī Viṭhṭhala Dattātreya Ghāṭe yañce adhyakshīya bhāshaṇa : Mahārāshṭra Sāhitya Sammelana, adhiveśana 36 vẽ, Amadābāda - Ghāṭe, Viṭhṭhala Dattātreya, 1875-1978 (SAMP early 20th-century Indian books project ;, 1953)
Presidential address delivered in the 36th annual Maharashtra Sāhitya Sammelana, held at Ahmedābād on 31st October, 1953.